The Sceptical Response to the Existential Problem of Systemic Suffering - Jonbäck, Francis (Open theology, 2021)
Recently, Yujin Nagasawa has argued that "systemic suffering" - suffering inherent in the evolutionary process - poses a problem for existentially optimistic theists and atheists who think that the world is overall good and therefore are happy and thankful to be alive in it. In short, he shows that it is difficult to consistently believe that the world is overall good when also recognising the existence of systemic suffering. In this article, I evaluate a sceptical response to the problem. The idea behind the response is a sort of scepticism according to which we do not know whether our knowledge about the realm of values is representative. I argue that the response fails, but that theism in conjunction with such scepticism succeeds. Atheism in conjunction with such scepticism, on the other hand, does not. I also argue that atheists can at least consistently hope that the world is overall good, despite systemic suffering. Finally, I answer objections and conclude.